Predictive analysis of independent learning bearing on students’ mathematics performance in Davao de Oro, Philippines - Cabilan, Judiel B.; Peteros, Emerson D. (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
The abrupt transition from face-to-face to remote learning due to the COVID-19 pandemic has made independent learning the dominant pedagogical framework globally. As students return to in-person education, there is an increasing expectation for them to demonstrate autonomy in their learning and its impact on academic outcomes. This study aims to evaluate students' level of independent learning across cognitive, metacognitive, and motivational strategies, assess their mathematics performance, and identify which learning strategies predict their performance in mathematics. A descriptive correlational research design was employed to examine the independent learning levels and mathematics performance of secondary school students in Davao de Oro, Philippines. The findings revealed that the students exhibited high levels of independence in their mathematics learning, particularly in cognitive, metacognitive, and motivational strategies, with metacognitive strategies receiving the highest ratings. Additionally, students achieved very satisfactory results in their mathematics courses. A multiple linear regression analysis identified that only cognitive and motivational strategies significantly predicted mathematics performance, with motivational strategies emerging as the strongest predictors. In contrast, metacognitive strategies were found to be non-significant predictors, which contradicts existing literature. These findings provide valuable insights for educational stakeholders to enhance students' independent learning, specifically focusing on cognitive and motivational strategies, to further improve mathematics performance.